2006
DOI: 10.1111/j.1532-5415.2006.00745.x
|View full text |Cite
|
Sign up to set email alerts
|

Research Agenda for Frailty in Older Adults: Toward a Better Understanding of Physiology and Etiology: Summary from the American Geriatrics Society/National Institute on Aging Research Conference on Frailty in Older Adults

Abstract: Evolving definitions of frailty, and improved understanding of molecular and physiological declines in multiple systems that may increase vulnerability in frail, older adults has encouraged investigators from many disciplines to contribute to this emerging field of research. This article reports on the results of the 2004 American Geriatrics Society/National Institute on Aging conference on a Research Agenda on Frailty in Older Adults, which brought together a diverse group of clinical and basic scientists to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
887
2
74

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,332 publications
(1,020 citation statements)
references
References 50 publications
19
887
2
74
Order By: Relevance
“…A question raised is how to use the finding that frailty is a risk factor for poor surgical outcome. It could be used to restrict access of frail patients to major surgery, although this is somewhat constraining given the increasing proportion of older and frail patients58. It could enable more individual risk assessment, discussion and consent to take place, or indeed allow targeted preoperative optimization of patients.…”
Section: Discussionmentioning
confidence: 99%
“…A question raised is how to use the finding that frailty is a risk factor for poor surgical outcome. It could be used to restrict access of frail patients to major surgery, although this is somewhat constraining given the increasing proportion of older and frail patients58. It could enable more individual risk assessment, discussion and consent to take place, or indeed allow targeted preoperative optimization of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although the underlying mechanism for frailty is likely multisystemic, the activation of inflammatory pathways is likely to play a central role in its development and its related vulnerability to adverse health outcomes (Walston et al 2006). In this study, we confirmed and extended initial findings by demonstrating that IL-10 tm/tm mice have significantly increased levels of several inflammatory cytokines, higher levels of IGF-1 at midlife, and found that they had higher mortality rates when compared to age and sex-matched B6 control mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although IL-10 and IFN-Îł levels have not been extensively studied in human population studies on aging and frailty, in part because of limitations in measuring serum samples that have been stored for long periods of time, investigators have reported significant elevations in macrophages and other inflammatory cells in frail compared to non-frail humans (Leng et al 2009;Yao et al 2011). The chronic inflammatory pathway activation observed in frail, older adults is likely multifactorial and stems from chronic disease states, altered body composition, and increased production of free radicals rather than a deficit in IL-10 ( Walston et al 2006). Aging mice of any strain likely have similar age-related inflammatory stimulation, but the IL-10 tm/tm frail mouse has a genetic disposition to increased inflammatory reactivity to any stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, for instance healthy life expectancy at age 60 years is 16.5 (LE 20.8 years) for women and 14.2 years for men (LE 18 years) [3]. However, many older adults develop chronic diseases and disability as they age, and have poor quality of life in their later years [4][5][6].…”
Section: Introductionmentioning
confidence: 99%